Improving students' physical fitness through creative gymnastics training methods - Marsuna, Marsuna; Rusli, Muhammad; Asshagab, Muhtar; Jud, Jud; Ratnanda, Olivia (Jurnal Patriot, 2024)
Problems: The problem that occurs is that many students are less interested in participating in sports activities, including creative gymnastics, because they are more accustomed to passive activities such as playing gadgets. Physical activity is often considered boring or tiring. Some schools may not have adequate sports facilities, such as large spaces, sports equipment, or access to trained trainers for creative gymnastics. This can limit the implementation of creative gymnastics optimally. Purpose: The purpose of this study is to determine the increase in students' physical fitness through the creative gymnastics training method. Methods: The type of research is quantitative with an experimental type by providing a pretest, treatment, and posttest. The sample in this study were 30 students of SMK Negeri 5 Konawe Selatan who had a hobby in the field of gymnastics. The test instrument used was a physical fitness test aged 16 to 19 years consisting of 5 test items, namely a 60-meter running test, 60-second elbow bend hanging, 60-second sitting lying, vertical jump, and 1000-meter running. The training method used with creative gymnastics was carried out 3 times a week with moderate, heavy, and light intensity. Data analysis techniques with SPSS version 20 analysis, by searching for descriptive data analysis, normality test, homogeneity test, and t-test. Results: Based on table 5 data analysis obtained a value of 13.489> 0.000, it can be concluded that there is a significant influence on improving students' physical fitness through the creative gymnastics training method. Conclusion: Creative gymnastics, which involves creative and dynamic movements, can improve physical fitness components such as strength, agility, endurance, flexibility, and coordination. In addition, this method also encourages students to be more active, involved, and enjoy physical activity, because creative variations of movements can increase motivation and interest.